Identification of Native and Posttranslationally Modified HLA‐B*57:01‐Restricted HIV Envelope Derived Epitopes Using Immunoproteomics. Issue 12 (10th April 2018) - Ramarathinam, Sri H.; Gras, Stephanie; Alcantara, Sheilajen; Yeung, Amanda W.S.; Mifsud, Nicole A.; Sonza, Secondo; Illing, Patricia T.; Glaros, Elias N.; Center, Robert J.; Thomas, Shane R.; Kent, Stephen J.; Ternette, Nicola; et al.
Abstract: The recognition of pathogen‐derived peptides by T lymphocytes is the cornerstone of adaptive immunity, whereby intracellular antigens are degraded in the cytosol and short peptides assemble with class I human leukocyte antigen (HLA) molecules in the ER. These peptide‐HLA complexes egress to the cell surface and are scrutinized by cytotoxic CD8+ T‐cells leading to the eradication of the infected cell. Here, naturally presented HLA‐B*57:01 bound peptides derived from the envelope protein of the human immunodeficiency virus (HIVenv) are identified. HIVenv peptides are present at a very small percentage of the overall HLA‐B*57:01 peptidome (<0.1%) and both native and posttranslationally modified forms of two distinct HIV peptides are identified. Notably, a peptide bearing a natively encoded C‐terminal tryptophan residue is also present in a modified form containing a kynurenine residue. Kynurenine is a major product of tryptophan catabolism and is abundant during inflammation and infection. Binding of these peptides at a molecular level and their immunogenicity in preliminary functional studies are examined. Modest immune responses are observed to the modified HIVenv peptide, highlighting a potential role for kynurenine‐modified peptides in the immune response to HIV and other viral infections.